miR-133b regulates proliferation and apoptosis in high-glucose-induced human retinal endothelial cells by targeting ras homolog family member A - Yao, Jun (Int J Mol Med, 2018)
The aim of the present study was to investigate the role of microRNA (miR)-133b in high-glucose-induced human retinal endothelial cells (hRECs), particularly regarding its potential targeting of ras homolog family member A (RhoA). To establish the high-glucose-induced diabetic retinopathy (DR) model, hRECs were cultured in high-glucose medium for 1, 2 and 3 days. An Annexin allophycocyanin (APC)/7-aminoactinomycin D (7-AAD) staining assay was performed to measure the apoptosis of hRECs. Next, the cells were transfected with miR-133b inhibitors or mimics, and the cell proliferation and apoptosis were measured by MTT and Annexin-APC/7-AAD staining assays, respectively. In addition, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), western blotting and immunocytochemistry were used to detect the expression levels of RhoA, Rho-associated protein kinase 1 (ROCK1), LIM domain kinase 1 (LIMK), myosin light chain (MLC) and phosphorylated (p)-MLC. It was observed that high-glucose or miR-133b inhibitor treatment attenuated the apoptosis of hRECs, and upregulated the mRNA and protein expression levels of RhoA, ROCK1 and LIMK, as well as the p-MLC protein level, in the hRECs. However, miR-133b overexpression inhibited the cell proliferation, promoted apoptosis, and downregulated the mRNA and protein levels of RhoA, ROCK1 and LIMK, as well as p-MLC protein, in high-glucose-induced hRECs. In conclusion, overexpression of miR-133b inhibited the proliferation and promoted apoptosis in a DR cell model by downregulating RhoA expression.